The Theory and Practice for Children's Contextualized Learning of Their First Language - Jilin, Li (Springer Berlin Heidelberg, 2018)
This book discusses situational instruction - a topic that is particularly relevant to Chinese language teaching and learning - in the context of research in the field. Employing real-world classroom case studies, it focuses on contextualized literacy, reading and writing. It also includes the findings of studies by practitioners with over 30 years of practical research experience, providing a valuable resource for anyone with an interest in Chinese teaching.